Research with farmers for farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Trypanosomiasis is one of the most severe livestock diseases in Africa: over 45 million cattle and 100 million sheep and goats are exposed to the disease across an area of 10 million km2. In south-west Ethiopia, at least six million cattle are at...